Pyroptosis-Related Inflammasome Pathway: A New Therapeutic Target for Diabetic Cardiomyopathy - Cai, Zhengyao; Yuan, Suxin; Luan, Xingzhao; Feng, Jian; Deng, Li; Zuo, Yumei; Li, Jiafu (Frontiers in Pharmacology, 2022)
Pyroptosis is a highly specific type of inflammatory programmed cell death that is mediated by Gasdermine(GSDM). It is characterized by inflammasome activation, caspase activation, and cell membrane pore formation. Diabetic cardiomyopathy(DCM) is one of the leading diabetic complications and is a critical cause of fatalities in chronic diabetic patients, it is defined as a clinical condition of abnormal myocardial structure and performance in diabetic patients without other cardiac risk factors, such as hypertension, significant valvular disease, etc. There are no specific drugs in treating DCM despite decades of basic and clinical investigations. Although the relationship between DCM and pyroptosis is not well established yet, current studies provided the impetus for us to clarify the significance of pyroptosis in DCM. In this review, we summarize the recent literature addressing the role of pyroptosis and the inflammasome in the development of DCM and summary the potential use of approaches targeting this pathway which may be future anti-DCM strategies.